REMOVAL OF SOX AND NOX FROM FLUE-GAS WITH CERIA - CHOI, E; LEE, JK; PARK, D; PARK, WH (KOREAN INST CHEM ENGINEERS, 1994)
Ceria (CeO2) is considered as one of materials for the simultaneous removal of SO(x) and NO(x) from flue gas. Ceria was coated on honeycomb and tested for adsorption of SO2 and reduction of NO with ammonia. Experimental results showed the characteristics similar to copper oxide but reactivity for NO reduction was higher in broader temperature range compared with the latter.